2016
DOI: 10.1152/ajpheart.00651.2014
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR-124 and miR-141 in the regulation of vascular reactivity and the relationship to RhoA and Rac1 after hemorrhage and hypoxia

Abstract: of miR-124 and miR-141 in the regulation of vascular reactivity and the relationship to RhoA and Rac1 after hemorrhage and hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…This might be the first study demonstrating the role of GAS5‐miR‐124‐ICAM‐1 axis in aggravating hypoxia injury. miR‐124 has been showed to participate in the modulation of vascular reactivity via altering expression of RhoA and Rac1 proteins, after hypoxia and hemorrhage . miR‐124 also plays a neuroprotective role in cerebral ischemic stroke through apoptosis‐inhibiting pathway, which is consistent with our data that miR‐124 overexpression dramatically impaired the apoptosis‐promoting effect of GAS5.…”
Section: Discussionsupporting
confidence: 90%
“…This might be the first study demonstrating the role of GAS5‐miR‐124‐ICAM‐1 axis in aggravating hypoxia injury. miR‐124 has been showed to participate in the modulation of vascular reactivity via altering expression of RhoA and Rac1 proteins, after hypoxia and hemorrhage . miR‐124 also plays a neuroprotective role in cerebral ischemic stroke through apoptosis‐inhibiting pathway, which is consistent with our data that miR‐124 overexpression dramatically impaired the apoptosis‐promoting effect of GAS5.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, in peripheral tissues and several cancer cell lines, several studies report direct targeting of EGR1 by miR-543 (Zhu et al, 2016), miR-192 (Wu et al, 2016), miR-146a (Contreras et al, 2015), miR-7578 (Zhang et al, 2013), miR-183 (Sarver et al, 2010), or miR-124 (Liu et al, 2016; Wang et al, 2016). Interestingly, the latter is highly expressed in the brain and is a critical regulator of neuronal function and thus an important mediator of neuroadaptations in response to chronic stress, reward and learning and memory (Sun et al, 2015).…”
Section: Functions and Regulations Of Egr1mentioning
confidence: 99%
“…Furthermore, a recent investigation of miRNA directly regulated by EGR1 in the human erythroleukemia cell line K562 reported a total of 124 distinct miRNA and 63 pre-miRNA bound by EGR1 following stimulation by phorbol ester—which activates EGR1 expression in this cell line (Wang et al, 2010). One of these miRNA, miR-124, is of particular interest as it is a known regulator of EGR1 levels (Liu et al, 2016; Wang et al, 2016), including in the central nervous system (Yang et al, 2012), and is tightly associated with neuronal function and higher order processes (Sun et al, 2015). Therefore, in addition to represent a likely mediator in EGR1 control of neuronal activity, these observations suggest that miR-124 could be involved in a negative feedback loop controlling EGR1 expression at the post-transcriptional level.…”
Section: Functions and Regulations Of Egr1mentioning
confidence: 99%
“… Coskunpinar et al (2016) reported an elevated level of circulating miR-221-3p in early AMI and found its significant correlation with troponin and LV systolic function. miR-124 has been illuminated promote cell death and apoptosis induced by myocardial ischemia-reperfusion ( Liu L. et al, 2016 ; Liu et al, 2019 ). Guo et al (2017) illustrated an upregulation of miRNA-124 and a positive correlation of miR-124 with cTnI and CK-MB in peripheral blood.…”
Section: Circulating Mirnas Function As Diagnostic and Prognostic Biomentioning
confidence: 99%